2015
DOI: 10.1016/j.bbadis.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of exosome generation with GW4869 dampens the sepsis-induced inflammation and cardiac dysfunction

Abstract: Sepsis is an infection-induced severe inflammatory disorder that leads to multiple organ failure. Amongst organs affected, myocardial depression is believed to be a major contributor to septic death. While it has been identified that large amounts of circulating pro-inflammatory cytokines are culprit for triggering cardiac dysfunction in sepsis, the underlying mechanisms remain obscure. Additionally, recent studies have shown that exosomes released from bacteria-infected macrophages are pro-inflammatory. Hence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
321
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(340 citation statements)
references
References 45 publications
14
321
5
Order By: Relevance
“…Indeed, they found that systemically administration of GW4869 could reduce the total exosomes in serum and treat allergic, cardiac and Alzheimer's dysfunction 29, 30, 31. Thus, our findings provide a potential method to prevent endothelial inflammation and atherosclerosis.…”
Section: Discussionmentioning
confidence: 64%
“…Indeed, they found that systemically administration of GW4869 could reduce the total exosomes in serum and treat allergic, cardiac and Alzheimer's dysfunction 29, 30, 31. Thus, our findings provide a potential method to prevent endothelial inflammation and atherosclerosis.…”
Section: Discussionmentioning
confidence: 64%
“…The treatment of Cancer-associated fibroblasts by GW4869, an inhibitor of exosome release blocking exosome secretion [24], significantly reduced the survival of co-cultured epithelial cells, demonstrating an important role of cancer-associated fibroblast exosomes in chemotherapeutic drug resistance. These findings suggested the potential of exosome inhibitors as treatment options alongside other therapies [25].…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic light scattering of A1-CM (Figure 2(a), Control A1-CM) revealed abundant EVs within the size range typical for mammalian exosomes and microvesicles (mean diameter: 161.5 nm; modal diameter: 128.6 nm). In mammalian cells, inhibition of the ceramide synthesis pathway using a small molecule inhibitor, GW4869, which targets neutral sphingomyelinase-2 (nSMase2), suppresses exosome secretion [32,33]. A1-EV levels were significantly reduced within the A1-CM in a GW4869 dose-dependent manner (Figure 2(a,b)): at 40 and 100 µM GW4869, two- and fivefold decreases in EV production were observed, respectively.…”
Section: Resultsmentioning
confidence: 99%